The Influence of Digital Detox Retreat on Psychological Well-Being and Sleep Quality of College Students in the Post-Pandemic Era - Nashit, Tazkia Adiba (PELNUS | Pen en Light for Natural Union of Science, 2025)
The rapid growth of digital technology has profoundly shaped the lifestyles of college students, particularly following the COVID-19 pandemic, which increased dependence on online learning and social media. While digital tools offer educational and social benefits, excessive screen exposure has been linked to stress, poor mental health, and disrupted sleep. This study aimed to examine the influence of a digital detox retreat on the psychological well-being and sleep quality of college students in the post-pandemic era. This study employs a quantitative experimental research design to examine the influence of a digital detox retreat on the psychological well-being and sleep quality of college students in the post-pandemic era. Participants consisted of 60 college students divided equally into experimental and control groups. The experimental group participated in a five-day digital detox retreat that restricted digital device use and incorporated mindfulness, outdoor activities, and reflective sessions. Data were collected using Ryff’s Psychological Well-Being Scale and the Pittsburgh Sleep Quality Index (PSQI), and analyzed using paired and independent t-tests. The results indicated significant improvements in the experimental group’s psychological well-being, characterized by lower stress levels and higher life satisfaction. Qualitative feedback revealed increased awareness and self-regulation of digital use after the retreat. These findings suggest that structured digital detox interventions can effectively enhance mental and physical well-being among college students by reducing digital overload and promoting healthier lifestyle habits. In conclusion, digital detox retreats represent a practical and low-cost strategy to improve psychological resilience and sleep hygiene in higher education settings. The study underscores the importance of mindful technology use and periodic digital disconnection as preventive measures against the adverse effects of excessive screen exposure in the digital era.